Analisis Prediktif Pemeliharaan Minyak Transformator Menggunakan Metode Markov - Surya Subaga, I.G.; Manuaba, I.B.G.; Sukerayasa, I.W. (Jurnal SPEKTRUM; Vol 6 No 4 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i04.p14, 2019)
As one of the main assets that play an important role in the distribution of electricity, the performance of the transformer must be maintained in prime condition. Damage to the transformer insulation oil often causes failure of the transformer. Damage to transformer oil is very difficult to predict, therefore monitoring its condition is very important to do. Dissolved Gas Analysis (DGA) is one og the method to determine the condition of transformer oil, where this method can analyze the condition of the transformer based on the concentration of gas dissolved in oil. A reguler maintenance of transformer oil can prevent the transformer oil from damage or failure of insulation. However, sometimes maintenance is carried out not in a right time that results in a decrease in transformer’s lifetime. In this analysis the value of Total Dissolved Combustible Gas (TDCG) was used to calculate transfomer’s reliability and availability value. Those value then processed using the Markov method to determine the possibilities of proper maintenance time. From the calculation results in this analysis the transformer reliability value in 30 days is 0.886, then the probability of decreasing the reliability value every month is 11.4%. And the value of the availability of the transformer is 0.803 or equal to 293 days. Based on this analysis, in one year the transformer operated properly for 293 days while 72 days the transformer was in an unfavorable condition. So that maintenance should be carried out in 293 days transformer’s condition can be maintained properly.